Use of Crossword Media to Increase the Arabic Vocabulary of Higher Class in Elementary School - Taqqiyyuddin, Taqqiyyuddin; Barzegar, Somayeh; Islam, Md. Saiful (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to achieve the following objectives: Planning: Describe the planning process for utilizing Crossword Puzzle media to enhance the Arabic vocabulary of fifth-grade students at Madrasah Ibtidaiyah Nahdlatul Ulama’ (MINU) Maudlu’ul Ulum Pandean Malang. Implementation: Detail the implementation of Crossword Puzzle media to increase the Arabic vocabulary of class V students at MINU Maudlu’ul Ulum Pandean Malang. Evaluation: Provide insights into the evaluation of the effectiveness of Crossword Puzzle media in enhancing the Arabic vocabulary of class V students at MINU Maudlu’ul Ulum Pandean Malang. Methodology: The research adopts a qualitative descriptive approach within the framework of classroom action research. The study comprises four stages: planning, implementation, observation, and reflection. Two cycles were conducted, involving a total of four meetings. Data collection methods include observation, interviews, and documentation. Triangulation is employed to ensure data validity. The research draws from a sample of class V students. Main Findings: The research demonstrates that the use of crossword puzzles effectively enhances the Arabic vocabulary of class V students. Success indicators include: Positive Student Engagement: During the learning process, students exhibit happiness and enthusiasm. Improved Assessment Results: Student performance shows significant improvement compared to their initial results. Pre-test completion rate: 44.4% Cycle I: 77.7%, Cycle II: 83% Novelty/Originality of this study: This study’s novelty lies in its potential as a reference tool for educators aiming to enhance the Arabic vocabulary of fifth-grade elementary school students using crossword puzzles.